XML Interaction effects of cerium oxide nanoparticles and trans-anethole on improving the function of damaged sciatic nerve in rat model - Zahra Naseri; Fariba Mamoudi; Khadijeh Haghighat (Fiyz̤, 2023)
Background: Sciatica is a peripheral nervous system disorder that affects many people throughout the world. New therapeutic approaches such as nanomedicines and plant derivatives with less side effects can be used to improve nerve tissue. Trans-anethole is a part of phytoestrogen derived from anise and fennel, and has strong steroidogenic and anti-inflammatory effects. Cerium oxide nanoparticles also have antioxidant properties. In this study, the interaction effects of cerium oxide nanoparticles and trans-anethole investigated on improving the function of the damaged sciatic nerve in a rat mode. Materials and method: In this study, 20 male rats weighing 250-300 g divided into five groups. The control group and the sciatica model group received saline. One group of sciatica model received simultaneous 125 mg/kg trans-anethole or 20 mg/kg cerium oxide nanoparticles, and the other group of sciatica model received simultaneous 250 mg/kg trans-anethole or 20 mg/kg cerium oxide nanoparticles (IP). Behavioral tests (Sensory and motor) taken from each group and muscle tissue removed to evaluate the atrophy rate. Results: The results showed that the simultaneous injection of trans-anethole and cerium oxide nanoparticles improved the damaged sciatic nerve compared to the sciatica model group. Also, the index of sciatica performance and sensory recovery was better in rats receiving trans-anethole and cerium oxide nanoparticles at the same time compared to the sciatica model group. Conclusion: Trans-anethole and cerium oxide nanoparticles, due to their antioxidant and neuroprotective properties, may be involved in the recovery of the damaged sciatic nerve by synergizing each other's effects.